EFEK PEMBERIAN JUS BUAH PISANG KEPOK (Musa paradisiaca forma typica) TERHADAP KADAR GLUKOSA DARAH TIKUS JANTAN GALUR WISTAR YANG TERBEBANI GLUKOSA - F. Eki Supra Bawati; Yunita Linawati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: This research aimed to determine the effects of administration of Musa paradisiacaforma typica juice on blood glucose levels and determine what dose of Musa paradisiaca formatypica juice which is most effective for lowering blood glucose levels in rats burdened glucose.This research was experimental with study with one way complete design using 25 male rats weredivided into five groups. Group I (negative control) was given CMC 1%, group II (positivecontrol) was given Glibenclamide dose of 0,64 mg/kgBW and group III, IV, V the rats were given5; 10; 20 mL/kgBW dose of Musa paradisiaca forma typica juice, all of the processes were giventhrough the oral method. Hypoglycemic effect of Musa paradisiaca forma typica juice was testedby following the Oral Glucose Tolerance Test (OGTT) method. The blood-glucose contents weretaken, at the 0 minutes before the OGTT and also taken at minutes of 15, 30, 60, 90, 120, 180, and240 after the OGTT, from the tested animal that had been gotten the pre-treatment of the negativecontrol, positive control and Musa paradisiaca forma typica juice before. Data of blood glucoselevels was statistically analyzed using one way ANOVA and Scheffe test with 95% convidencelevel. The result of this research showed that Musa paradisiaca forma typica juice can loweringblood glucose levels on rats in burdened glucose. Dose Musa paradisiaca forma typica juice aremost effective in lowering blood glucose levels in a dose was 10 mL/kgBW.Key words: Musa paradisiaca forma typica, blood glucose levels, OGTT